The Missing Link in Regional Integration in South Asia: The Case for Regional and Sub-regional Political Institutions. (September 2019) - Thangasamy, Andrew
Regional governance efforts in South Asia have been missing regional political institutions. There is no shortage of ideas and suggestions by scholars, practitioners, diplomats and others in terms of areas for integration in South Asia. And yet, regional integration continues in a piecemeal like stuttering fashion. Integration lags not because there are questions about the efficacy of regional integration or questions about where or what to integrate, it lags because of the path forward—in terms of how —is unclear. Regional or sub-regional political institutions vested with the decision-making authority can aid in integration better than the status quo. Political institutions in contrast to forums or summit-convening authorities can make decisions of their own benefiting the interests of those whom they represent. This article examines the current state of regional governance efforts in South Asia and evaluates the argument for regional and sub-regional political institutions.